Microstructural Changes in the Left Mesocorticolimbic Pathway are Associated with the Comorbid Development of Fatigue and Depression in Multiple Sclerosis. Issue 3 (1st February 2021) - Palotai, Miklos; Small, Catherine; Makris, Nikolaos; Somes, Nathaniel G.; Pinzon, Alfredo Morales; Rathi, Yogesh; Marzullo, Aldo; Levitt, James J.; Bakshi, Rohit; Chitnis, Tanuja; Guttmann, Charles R. G.
ABSTRACT: BACKGROUND AND PURPOSE: Lower reward responsiveness has been associated with fatigue in multiple sclerosis (MS). However, association of MS‐related fatigue with damage to the mesocorticolimbic reward pathway (superolateral medial forebrain bundle [slMFB]) has not been assessed. We investigated the association of fatigue and depression with slMFB damage in MS patients stratified based on longitudinal fatigue patterns. METHODS: Patient stratification: 1. Sustained Fatigue (SF): latest two Modified Fatigue Impact Scale (MFIS) ≥ 38 ( n = 26); 2. Reversible Fatigue (RF): latest MFIS < 38, and at least one previous MFIS ≥ 38 ( n = 25); 3. Never Fatigued (NF): ≥ 5 consecutive MFIS < 38 ( n = 42); 4. Healthy Controls ( n = 6). Diffusion MRI‐derived measures of fractional anisotropy (FA), axial (AD), mean (MD), and radial diffusivity (RD) of the slMFB were compared between the groups. Depression was assessed using the Center for Epidemiologic Studies‐Depression Scale (CES‐D). RESULTS: Depressed (CES‐D ≥ 16) SF patients showed significantly higher MD and RD than nondepressed SF and RF, and depressed RF patients, and significantly lower FA than nondepressed SF and depressed RF patients in their left slMFB. Depressed SF patients showed significantly higher left slMFB MD and AD than healthy controls. CONCLUSION: Microstructural changes to the left slMFB may play a role in the comorbid development of fatigue and depression in MS.